THE ROLE OF ARTIFICIAL INTELLIGENCE IN DEVELOPING THE PROFESSIONAL COMPETENCE OF A FUTURE TEACHER (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Improving knowledge and skills in artificial intelligence is currently becoming a major national priority. Developing these skills is also essential for future teachers. Furthermore, the use of artificial intelligence technologies helps teachers quickly and effectively analyze data, develop curricula that meet individual student needs, and optimize the learning process. At the same time, artificial intelligence offers extensive opportunities for developing pedagogical strategies and equipping teachers with the skills necessary for professional growth. This article analyzes articles on the competencies, literacy, and professional development of future teachers in this area, and attempts to explore the relationship between these concepts and digital competencies and digital literacy.